Distribution of Radiation in Erbil city - Abdulkareem, Nashwan Karkhi; Abdula, Tara Nuradin; Abdula, Niaz Salh; Ahmad, Dhahir Tahir (Diyala Journal of Medicine, 2019)
Background: Radiation is the emission or transmission of energy in the form of waves or particles through space or through a material medium. This includes electro-magnetic radiation such as radio waves, visible light, and x-rays, particle radiation such as α, β, and neutron radiation and acoustic radiation such as ultrasound, sound, and seismic waves. Radiation may also refer to the energy, waves, or particles being radiated. Some studies design to estimate the distribution of radiation in different streets and effect on health environment. Objectives: To determine the magnitude of radiation in different streets in Erbil city and demonstrate the difference between them. Methods and Materials: Palm RAD meter-nuclear radiation meter at Model-907) was used for investigation of radiation in different streets in Erbil city like (around citadel, 30m, 60m, 40m and 100m) A nuclear radiation meter is an instrument measures the nuclear radiation. In other hands it is used to detect the radiation in the spaces near the sources of radiation like (X-ray, CT-Scanner and others) at streets of Hospital, centers of bone fracture imaging are transmitted where nuclear radiation and x-ray radiation to the outside to the environment surrounding radiation sources. Which induces biological effects is more than standard value. Results: The results showed that the nuclear radiation at small dose is present and detected in the different streets in Erbil city, but more dose are detected in the space near sources of radiation which are mentioned in the previous words. This increasing of nuclear radiation which is caused by sources of radiation like (X-ray, CT-Scanner, and the bomb of USA) included to biological and physiological effects on the people in Erbil city who are sting and working near these places is showed by statistical test. Conclusion: Distribution of radiation is dependent on the sources of radiations doses, and discussing that to investigate how this radiation affects the physiology of human body and showing the disadvantage of increasing and decreasing of radiation with the location of people.